PUBLIC FINANCE AND FISCAL POLICY IN INDONESIA: AN ISLAMIC AND COMPARATIVE GLOBAL PERSPECTIVE - khusnul hotima; hurriyatus saidah (Assets Journal: Journal of Economic and Business, 2026)
his paper examines the dynamics of public finance and fiscal policy in Indonesia, with a particular focus on integrating Islamic financial principles and offering a comparative perspective with global fiscal strategies. It explores how Indonesia's fiscal policies are influenced by both traditional economic models and Islamic finance, emphasizing the role of Shariah-compliant financial instruments in public sector management. Through a comparative analysis with global fiscal frameworks, the study highlights the effectiveness of fiscal responsibility, government budgeting, taxation systems, and public expenditure management in fostering economic growth and stability. The paper also addresses the role of fiscal decentralization, government debt, and sustainable development in shaping Indonesia's economic future. By drawing insights from international best practices, the study proposes avenues for improving Indonesia's fiscal policies while aligning them with Islamic economic values.